EFFECTIVENESS OF FIRST AID AND OSH TRAINING ON IMPROVING THE KNOWLEDGE OF KINDERGARTEN TEACHERS IN GRESIK - Neffrety Nilamsari; Ratih Damayanti (Journal of Industrial Hygiene and Occupational Health, 2018)
In Indonesia every year, 750,000 children die from accidents and 400 million children are seriously injured. In 2010 child mortality due to accidents, poisoning and trauma in Indonesia was recorded at 7.3% and was one of the five highest causes of child mortality. Accidents can be prevented and can be overcome if the teacher knows what to do to prevent and provide first aid in accidents or medical emergencies. The purpose of this study was to identify the average value of kindergarten teacher knowledge about occupational safety and health (OSH) in the school environment before and after training to improve first aid and OSH knowledge and skills. This type of research is quasy exprimental with one group pre test and post test design research design. The population is all kindergarten teachers in Menganti District, Gresik Regency. The purposive sampling technique was 20 teachers who were representatives of 3 HIMPAUDI clusters. Results of the study Before and after training participants were given a questionnaire aimed at knowing participants' understanding of knowledge and materials about first aid and knowledge of occupational safety and health (OSH). The average knowledge before first aid training was 65.75 while after the training it increased to 89.75.The average knowledge about OSH before training was 61.5 and after training increased to 90. The results of paired test tests obtained p value> 0.005 that is 0.000 which means that there is a very significant mean difference between before and after the provision of first aid and OSH training in school environments . It can be said that the training can increase the knowledge of playgroup teachers who are trainees about first aid knowledge and knowledge about OSH in the school environment. First Aid and OSH training can improve knowledge of kindergarten teachers at Menganti District, Gresik.Keywords: First aid, Ocupational Health and Safety, Knowledge , Kindergarten teacher